Field studies of PERC and Al-BSF PV module performance loss using power and I-V timeseries - Curran, Alan J.; Yu, Xuanji; Liu, Jiqi; Colvin, Dylan J.; Iqbal, Nafis; Moran, Thomas; Brownell, Brent; Li, Mengjie; Davis, Kristopher O.; Huey, Bryan D.; Jaubert, Jean-Nicolas; Braid, Jennifer L.; et al. (Frontiers in Energy Research, 2023)
We have studied the degradation of both full-sized modules and minimodules with PERC and Al-BSF cell variations in fields while considering packaging strategies. We demonstrate the implementations of data-driven tools to analyze large numbers of modules and volumes of timeseries data to obtain the performance loss and degradation pathways. This data analysis pipeline enables quantitative comparison and ranking of module variations, as well as mapping and deeper understanding of degradation mechanisms. The best performing module is a half-cell PERC, which shows a performance loss rate (PLR) of −0.27 ± 0.12% per annum (%/a) after initial losses have stabilized. Minimodule studies showed inconsistent performance rankings due to significant power loss contributions via series resistance, however, recombination losses remained stable. Overall, PERC cell variations outperform or are not distinguishable from Al-BSF cell variations.